Prevalência da comorbidade psiquiátrica em dependentes de drogas de abuso atendidos nos Centros de Atenção Psicossocial Álcool e Drogas do Estado de Sergipe - Andrade, Joyce Dalline Silva (2014)
The consumption of psychoactive substances is a serious public health problem worldwide, including in various regions of Brazil. The abuse of these substances (drugs of abuse) often relates the self-destruction of its users, with consequent mental changes that can lead to violence, indifference, isolation and contempt. In its turn, prolonged use can lead to the development of the phenomenon of dependence and the existence of psychiatric Comorbidities. Thus, the objective of this study was to establish the epidemiological profile of drug of abuse addicts which are served by the health system through the Centros de Atenção Psicossocial Álcool e Drogas (CAPS AD) located in Sergipe-important State in the Northeast region of Brazil-and also investigate the prevalence of major risk factors associated with the occurrence of comorbidity of psychiatric disorders and addiction. It is a regional study, a multicenter, cross-sectional, conducted with four CAPS AD patients from January 2013 to October 2013. The study included all patients over 18 years of age, with a clinical diagnosis of dependence on one or more psychoactive substances and they respond to treatment in institutions for at least a month. The epidemiological profile of the population studied and the variables: psychiatric symptoms and use of psychoactive substances were evaluated through standardized instruments. The total sample consisted of 103 patients who were distributed with proportional allocation and it was characterized by a predominance of males (91.27%), the average age of patients was 37.9 ± 9.1 with predominant age group between 30 and 59 (80.55%). About 16.50% were illiterate and 75.73% had primary education, 61.16% were single, 30.09% were unemployed and 33.0% did not have formal employment relationship. The first experience with drugs was in preadolescence (40.78%) and adolescence (34.95%) alcohol (70.87%) nicotine (18.46%) the drugs of first contact. Approximately, 27% were alcohol dependents, 11% of cocaine and/or crack and 62% were dependent on multiple drugs. Major depressive episode (69.90%), risk of suicide (66.01%) and anxiety disorders (63.10%) were the most diagnosed disorders in that population. In its turn, vehicular driving under the influence of drugs (55.10%) and imprisonment or detention (63.10%) were the most frequent risk behaviors. In addition, there was a statistically significant correlation between suicide risk and psychiatric comorbidities (p <0.05). Thus, the dependence on drugs of abuse reaches individuals of a wide age group and, with early effect, may cause negative effects due to psychoactive substance dependence in people with severe mental disorders, such as clinical and social evolution impaired.